KONTRIBUSI HASIL TANGKAPAN IKAN DALAM PENDAPATAN RUMAH TANGGA MASYARAKAT DI SUNGAI DESA RADEN ANOM, KECAMATAN BATANG ASAI - Wijaya, Jogi; Farizal, Farizal; Hariski, M.; Heltria, Septi; Ramdhani, Farhan (Jurnal Perikanan Unram, 2025)
The phenomenon of the relatively small income of the fishing community so that it is not able to meet the needs of fishermen's households, this situation makes fishermen have to have an additional source of income to be able to meet their household needs. Efforts that can be made by fishermen in Raden Anom Village, Batang Asai District are to catch fish in the Batang Asai River. The people in Raden Anom Village, Batang Asai District have their main jobs as farmers, laborers and self-employed. In addition to the community having the main job, some people in Raden Anom Village also carry out fishing activities in the Batang Asai River. This study aims to determine the contribution of fish catches to the household income of the community in Raden Anom Village, Batang Asai District. The method used in this study is a survey method with the analysis used is descriptive. The respondents to this study were obtained by census of 15 people (100%) fishermen with the data collection instrument being a questionnaire. The results of the research showed that the livelihood patterns of the people in Radon Anom Village, Batang Asai District were diverse, ranging from builders as fishermen, rubber plantations as well as fishermen, motorcycle repair shops as well as fishermen and members of the wallet as well as fishermen. The contribution of income that is dissipated is from non-fish activities, namely as a member of the wallet of Rp. 4,987,500 with a very high category, while the contribution of income from fish activities or from fishing is those that have a livelihood pattern as fishing as well as as a builder, which is Rp. 1,215,000 with a low category